2023
DOI: 10.1002/pc.27302
|View full text |Cite
|
Sign up to set email alerts
|

Low‐velocity impact response and damage tolerance of hybrid biaxial/triaxial braided composite laminates

Abstract: The structural properties of braided composite laminates are significantly affected by the low‐velocity impact (LVI). In this paper, the impact resistance and damage tolerance of triaxial braid structure laminates at different positions were mainly studied. Three hybrid biaxial (B)/triaxial (T) braided composite structures of BBTT, BTTB, and TTBB were designed, and LVI test and post‐impact compression tests were carried out. The results show that the triaxial braided fabric with quasi‐isotropic on the impact s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…The UC specimen had a higher impact load and displacement at the first peak compared to that of the discontinuous specimen. The displacements of the three types of specimen with an impact energy increasing to 9 J are the same before reaching the second peak; however, the displacement of the UC specimen drops sharply because of fiber breakage or the delamination of the specimen 9,30 . This implies that the discontinuous structure does not play a role in reducing the damage at the first peak, whereas it works at the second peak.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The UC specimen had a higher impact load and displacement at the first peak compared to that of the discontinuous specimen. The displacements of the three types of specimen with an impact energy increasing to 9 J are the same before reaching the second peak; however, the displacement of the UC specimen drops sharply because of fiber breakage or the delamination of the specimen 9,30 . This implies that the discontinuous structure does not play a role in reducing the damage at the first peak, whereas it works at the second peak.…”
Section: Resultsmentioning
confidence: 94%
“…The displacements of the three types of specimen with an impact energy increasing to 9 J are the same before reaching the second peak; however, the displacement of the UC specimen drops sharply because of fiber breakage or the delamination of the specimen. 9,30 This implies that the discontinuous structure does not play a role in reducing the damage at the first peak, whereas it works at the second peak. This indicates that greater stress can be borne by the overlap structure at the same deformation, and more impact energy can be converted into the elastic potential energy, 31 which improves the impact resistance of the specimen.…”
Section: Impact Response Of Various Laminatesmentioning
confidence: 99%
“…1,2 The LVI of laminated composites has been extensively discussed in the literature. [3][4][5][6][7][8][9][10] For instance, Sun and Hallett 3 numerically and experimentally investigated the impact damage occurred in two different layups of CFRP laminates. Results revealed that the single-ply layup, [45/0/90/À 45] 4S , indicated a higher critical load and consequently a delayed delamination propagation compared with the blocked-ply laminate, [45 2 /0 2 /90 2 / À 45 2 ] 2S .…”
Section: Introductionmentioning
confidence: 99%
“…The LVI of laminated composites has been extensively discussed in the literature 3–10 . For instance, Sun and Hallett 3 numerically and experimentally investigated the impact damage occurred in two different layups of CFRP laminates.…”
Section: Introductionmentioning
confidence: 99%
“…However, the lower strength of laminated structures in the thickness direction makes them highly susceptible to impact load, resulting in complex failure of the internal structure caused by barely visible impact damage. Consequently, this leads to a reduction in the residual compressive strength 3,4 . Under low‐velocity impact loads, composite materials exhibit a combination of failure modes, including matrix cracking, delamination, fiber fracture, and indentation 5,6 .…”
Section: Introductionmentioning
confidence: 99%